1987
DOI: 10.2307/1939891
|View full text |Cite
|
Sign up to set email alerts
|

Wind Dispersal Distances in Dimorphic Achenes of Ragwort, Senecio Jacobaea

Abstract: A mark-recapture study of wind-dispersed achenes of Senecio jacobaeo conducted in western Oregon showed that the proportion of achenes dispersing a given distance varied significantly with changes in site (inland vs. coastal), surroundings (mown vs. unmown), height of release (0-50, 50-100, 100-150, 150-200 cm), time of release (early vs late in the season), direction of dispersal, and achene type (disk vs. ray achenes). Influences of height of release, direction, achene type, and time of release were strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 26 publications
8
71
0
1
Order By: Relevance
“…This supports previous evidence that shrubs act as windbreaks and can reduce anemochory (McEvoy and Cox, 1987). Secondary dispersal was highest in disturbed areas and shrublands, i.e.…”
Section: Dispersal Steps and Agents -supporting
confidence: 91%
See 1 more Smart Citation
“…This supports previous evidence that shrubs act as windbreaks and can reduce anemochory (McEvoy and Cox, 1987). Secondary dispersal was highest in disturbed areas and shrublands, i.e.…”
Section: Dispersal Steps and Agents -supporting
confidence: 91%
“…These results confirm those of Johnston (2011) and Monty et al (Monty et al, 2013), who found even more important rates of secondary dispersal of B. tectorum in areas with almost no vegetation (reclamation and burned areas, respectively). Research on other species also found an influence of vegetation on ground level dispersal through a decrease in wind speed, changes in wind turbulence and seed entrapment (Chambers, 2000;Marushia and Holt, 2006;McEvoy and Cox, 1987).…”
Section: Dispersal Steps and Agents -mentioning
confidence: 97%
“…Para estas, fatores como a altura da árvore, a velocidade e a direção do vento (Isaac 1930;Horn et al 2001), a topografia e a vegetação adjacentes (Cremer 1965), e a umidade (McEvoy & Cox 1987) influenciariam a dispersão. Aparentemente, grande parte dessas variáveis atua uniformizando o investimento na dispersão em todas as direções e para a maior distância possível.…”
Section: Espécies (%)unclassified
“…Finally, the activator-inhibitor framework incorporates environmental disturbance, movement and spatial heterogeneity. This motivated the gathering of detailed information on movement showing that the relative dispersal ability of the host plant (McEvoy and Cox 1987) is much less than that of the natural enemy species [the cinnabar moth T. jacobaeae, the ragwort flea beetle L. jacobaeae, and the ragwort seed head fly Botanophila seneciella (Meade, 1892)] under field conditions (Harrison et al 1995;Rudd and McEvoy 1996). Thus, natural enemies can easily overtake and suppress a weed population spreading autonomously.…”
Section: Biological Control Of Weeds: Herbivore-plant Interactionsmentioning
confidence: 99%